The applications of POD method in dual rotor-bearing systems with coupling misalignment. (March 2021) - Lu, Kuan; Jin, Yulin; Huang, Panfeng; Zhang, Fan; Zhang, Haopeng; Fu, Chao; Chen, Yushu
Highlights: The dual rotor-bearing system with misalignment is established. POD method is the first time apply to dimension reduction of dual rotor-bearing system. Efficiency and accuracy of POD method is verified. Nonlinear characteristics of dual rotor-bearing system with misalignment are revealed. Abstract: In this paper, the proper orthogonal decomposition (POD) method is first time apply to the dimension reduction of dual rotor-bearing experiment rig which is similar to an aero-engine rotor. The basic theory of the POD method and the application in dynamical system are introduced. The supporting bearing nonlinearity and the coupling misalignment of high and low pressure rotors are considered, and the dynamical model is established by finite element method based on dual rotor experiment rig. The frequency behaviors of dual rotor-bearing coupling misalignment response are discussed via comparing the numerical and experiment results to verify the efficiency of the model. The POD method is used for dimension reduction of rotor-bearing system, and the dynamical behaviors of the reduced-order model (ROM) are compared with the full order system (FOM) and experiment to verify the higher computational efficiency and accuracy of the POD method. These results in this paper can provide engineering guidance to actual dual rotor-bearing system with coupling misalignment fault.